Genre innovations in modern ukrainian mass media - Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article expertly comments on the trend of genre innovations in modern Ukrainian mass media. The author's argumentation is based on the functional evolution of the literary language, which is reflected in the change of the style's communicative nature, in particular, media. Logically also in his genre system. The situation of genre forms' modeling according to the criteria of syncretism, updated in time and space of modern Ukrainian-language communication, is commented on, which is connected with the need of recipients to perceive information from the media not linearly, but constructively – multifaceted and variable. It results in the active emergence of genre variants, actualized in the media space, which modify its functional and stylistic resource and potential. Genre innovations are interpreted in the context of a professional analysis of language show genre new for national media, which appears as a communicative invariant of intellect show and is synchronized with the style of the edutainment format. Language factology attests the conceptualization of the cultural and linguistic context of social communication in Ukrainian language, which is based on current rules, established tradition, and transitional forms that undergo communicative adaptation. Thus, the novelty of the genre is formulated, which consists in the intellectual understanding of the communicative nature of Ukrainian language in media space. The mass audience gets an objective opportunity to participate in the comprehension and understanding of the processes that indicate the dynamics of the literary language, its norms and exceptions. The thesis is proved that new for the media language show genre is a syncretic phenomenon in terms of functional and stylistic resource and genre nature, which is based on a communicatively motivated combination of information and entertainment functions. Information in this case relies on the cognitive context of verbalization, as it concerns the actualization of cognitive processes of the development of mass language consciousness, which is provided by the creolized resource of media entertainment.
Keywords: media, genre, media communication, media genre, genre innovations, show, language show, cognition, entertainment, edutainment.